2012
DOI: 10.1186/1687-6180-2012-107
|View full text |Cite
|
Sign up to set email alerts
|

Development of band ratioing algorithms and neural networks to detection of oil spills using Landsat ETM+ data

Abstract: Accurate knowledge of the spatial extents and distributions of an oil spill is very impor-tant for efficient response. This is because most petroleum products spread rapidly on the water surface when released into the ocean, with the majority of the affected area becoming covered by very thin sheets. This article presents a study for examining the feasibility of Landsat ETM+ images in order to detect oil spills pollutions. The Landsat ETM+ images for 1 st , 10 th , 17 th May 2010 were used to study the oil spi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 13 publications
(18 reference statements)
1
26
0
Order By: Relevance
“…Lee et al [8] developed an algorithm for discriminating film-like oil from thick oil using DubaiSat-2 and Landsat Operational Land Imager (OLI) data. Taravat et al [9] performed ratio operations on Landsat 7 ETM images to enhance oil spill features. They concluded that the bands' difference between 660 and 560 nm, division at 660 and 560, and division at 825 and 560 nm, normalized by 480 nm, provide the best result.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [8] developed an algorithm for discriminating film-like oil from thick oil using DubaiSat-2 and Landsat Operational Land Imager (OLI) data. Taravat et al [9] performed ratio operations on Landsat 7 ETM images to enhance oil spill features. They concluded that the bands' difference between 660 and 560 nm, division at 660 and 560, and division at 825 and 560 nm, normalized by 480 nm, provide the best result.…”
Section: Introductionmentioning
confidence: 99%
“…To effectively and accurately predict and forecast an oil spill, it is strongly suggested that multiple satellite observations and hydrodynamic models integrated. With sophisticated algorithms, such as artificial neural networks (Taravat and Del Frate 2012), to classify oil spill and measure oil thickness, the efficiency of rapid responses for emergency oil spills can be significantly improved, and more active strategies to combat oil spills can be made.…”
Section: Resultsmentioning
confidence: 99%
“…The stripes in Landsat ETM+ data (caused by the SLC in the ETM+ instrument failed on 31 May 2003) have been removed according to Taravat et al [93]. Pixels not affected by striping are used to construct spline functions describing spatial grey level distributions of an image [93].…”
Section: Image Pre-processingmentioning
confidence: 99%
“…Pixels not affected by striping are used to construct spline functions describing spatial grey level distributions of an image [93].…”
Section: Image Pre-processingmentioning
confidence: 99%